Characterization of monoclonal antibodies against alpha-hemolysin of Escherichia coli. - Oropeza-Wekerle, R L (1991)
Monoclonal antibodies (MAbs) were raised against native and denatured alpha-hemolysin (HlyA) of Escherichia coli. Binding of the MAbs to native, denatured, and erythrocyte-complexed active wild-type hemolysin and mutant derivatives was tested. All 15 MAbs analyzed bound to native hemolysin, even when the toxin was complexed with human erythrocytes. While some MAbs were unable to bind to a specific native mutant hemolysin, others could not even bind to mutant hemolysin carrying deletions remote from their actual binding sites. A rough determination of the binding sites of 15 MAbs on HlyA was performed by Western immunoblot analysis using CNBr fragments of HlyA and mutant hemolysin proteins. Interestingly, the binding sites of the MAbs against native hemolysin seem to be more randomly distributed on HlyA than are those of MAbs against denatured hemolysin. Three MAbs inhibited the hemolytic activity significantly. Two of these MAbs bound to the hydrophobic region, and the other one bound to the repeat domain of HlyA. The use of synthetic peptides from these regions allowed determination of the linear epitopes for two of these MAbs.